Dioxins and human health in the light of present knowledge - Rajewski, Paweł; Rajewski, Piotr; Dobosz, Krzysztof M.; Hagner, Magdalena (Przewodnik Lekarza/Guide for GPs, 2007)
Dioxins constitute an enormous group of chemical substances (xenobiotics) alien to the environment. They have been entering the environment, for almost 100 years due to the production activity of man or together with chemical waste. Unlike other xenobiotics, dioxins have never been a product of intended or intentional human activity. Dioxins and their derivatives pose an important and so far underestimated threat to human health and life. They contribute to forming many pathologies including cancer, fetus defects and genetic defects. Their concentration in the atmosphere and food is growing gradually year by year, negatively affecting the natural environment and human population. Research into stopping or decreasing the toxic emission of these substances to the atmosphere and intensifying research into their influence on human life seem essential.